Camrelizumab, an Anti‐PD‐1 Monoclonal Antibody, Plus Carboplatin and Nab‐Paclitaxel as First‐Line Setting for Extensive‐Stage Small‐Cell Lung Cancer: A Phase 2 Trial and Biomarker Analysis - Jia Yu; Deyu Cai; Sha Zhao; Lei Wang; Xinlong Zheng; Anwen Xiong; Qi Wang; Bin Chen; Menghang Yang; Wei Li; Yan Wang; Jiajia Yuan; et al. (MedComm)
ABSTRACT This study aimed to investigate the efficacy, safety, and predictors of camrelizumab combined with carboplatin and nab‐paclitaxel as first‐line setting for patients with extensive‐stage small‐cell lung cancer (ES‐SCLC). Camrelizumab plus carboplatin and nab‐paclitaxel were administrated every 3 weeks for four to six cycles, followed by maintenance camrelizumab until intolerable toxicity or disease progression. The primary endpoint was 6‐month progression‐free survival (PFS) rate and secondary endpoints were objective response rate (ORR), disease control rate (DCR), PFS, overall survival (OS), and safety. We conducted the whole‐exome and transcriptomic sequencing on available tumor samples to explore the potential predictive biomarkers. A total of 60 patients were included. Primary endpoint was met with 6‐month PFS rate of 52.2%. The median PFS and OS were 7.1 and 18.1 months, respectively. The confirmed ORR and DCR were 73.3% and 93.3%, respectively. No unexpected adverse events were observed. Exploratory analysis showed that MUC17 alterations or high NEUROG1 expression were correlated with markedly shorter PFS and OS. Deeper investigation of transcriptomic data reveals two subsets with distinct immune features and therapeutic vulnerabilities. Collectively, this trial suggested that camrelizumab plus carboplatin and nab‐paclitaxel might be an alternative first‐line setting for ES‐SCLC. Integration of multiomic data could highlight the complex mechanisms underlying chemo‐immunotherapy responses.